Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1080/01904169209364508
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of phosphate absorption byStylosanthesspp. in the presence of aluminium

Abstract: The mechanisms of action by which aluminium affects phosphate absorption were evaluated in Stylosanthes guianensis (aluminium-sensitive)and Stylosanthes macrocephala (aluminium-tolerant), through kinetic studies with aluminium in pre-and co-treatment. Multiphasic and cooperative models of ions absorption were tested. In the absence of aluminium, S. guianensis, a specie which normaly requires more phosphorus, showed lower rates of phosphate absorption, which was attributed to slower turnover of the carrier. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…One toxic effect of the aluminum in plants is the interference in absorption of minerals, especially phosphorus (Foy et al, 1978;Machado et al, 1992;Marschner, 1995). The studies of the absorption kinetics in Stylosanthes, Machado et al (1992) concluded that the reduction in the absorption rate of phosphorus by aluminum cannot elucidate the physiological mechanism that grants some plants differential tolerance to this element, but a generalized action of aluminum in plasmalemma entail changes in phosphate transport system.…”
Section: Introductionmentioning
confidence: 99%
“…One toxic effect of the aluminum in plants is the interference in absorption of minerals, especially phosphorus (Foy et al, 1978;Machado et al, 1992;Marschner, 1995). The studies of the absorption kinetics in Stylosanthes, Machado et al (1992) concluded that the reduction in the absorption rate of phosphorus by aluminum cannot elucidate the physiological mechanism that grants some plants differential tolerance to this element, but a generalized action of aluminum in plasmalemma entail changes in phosphate transport system.…”
Section: Introductionmentioning
confidence: 99%